Quality of life among cancer patients on Chemotherapy in oncology unit HUSM - Yee, Yong Siew (2006)
Background of the study: Cancer is becoming a major health proble1n throughout the world and chemotherapy is one of the most important tools for its treatment. However, side effects of chemotherapy can influence patient's QOL (quality of life). In addition, physicians frequently underesti1nate patient's QOL. Accurate QOL information can make a major contribution to improve the management of cancer patients. It gives guidelines and awareness for clinicians and nurses to concentrate more on QOL and plan specific interventions to 1neet the needs in order to improve patients' QOL. Objective: To identify the frequency of side effects during chetnotherapy treatinent, compare the QOL pre- and on-chemotherapy treatment and determine the domains ofQOL (physical, mental and social) in relation to the three most common side effects of chemotherapy in HUSM. Methodology: This study was a cross-sectional design and descriptive study. Fifty heterogeneous cancer patients with chemotherapy treatment enrolled into this study. A modified version 3.0 of the EORTC QLQ-C30 was used with reliability alpha 0.829. Result: Results from this study revealed that the three most common side effects of chemotherapy were fatigue, alopecia and appetite alteration. There was a significant difference of QOL before and during chemotherapy. The three most common side effects were significantly correlated with domains of QOL except for alopecia which was related to physical domain. Overall, the global QOL of cancer patients were improved. Conclusion: Assessment and evaluation of QOL for cancer patients with chemotherapy is very important. Concentrating on QOL allows nurses to plan, implement, evaluate and revise QOL care during various treatment periods. Nurses can provide information for cancer patients regarding prevention and management strategies for side effects of chemotherapy.